If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4(2x + 8) = 36 Reorder the terms: 6x + -4(8 + 2x) = 36 6x + (8 * -4 + 2x * -4) = 36 6x + (-32 + -8x) = 36 Reorder the terms: -32 + 6x + -8x = 36 Combine like terms: 6x + -8x = -2x -32 + -2x = 36 Solving -32 + -2x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -2x = 36 + 32 Combine like terms: -32 + 32 = 0 0 + -2x = 36 + 32 -2x = 36 + 32 Combine like terms: 36 + 32 = 68 -2x = 68 Divide each side by '-2'. x = -34 Simplifying x = -34
| 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 | | 6x-27=4x+12 | | cx+5=dx-3 | | 5+2(x+1)=2n | | 9y+13=30 | | w^2-11=2-5w^2 | | 6x+40=8x-20 | | 5*x+2=11-x*8 | | 4b-8=1+6-3b-1 | | 2x^2+kx^2-2kx-16=0 | | 2x-(x+2)=2x-0.1 | | 6=7x-x+6 | | w*w+9=6w |